2010
DOI: 10.1002/jcp.22274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of anti‐inflammatory action of platelet‐rich plasma on human chondrocytes: Mechanisms of NF‐κB inhibition via HGF

Abstract: Loss of articular cartilage through injury or disease presents major clinical challenges also because cartilage has very poor regenerative capacity, giving rise to the development of biological approaches. As autologous blood product, platelet-rich plasma (PRP) provides a promising alternative to surgery by promoting safe and natural healing. Here we tested the possibility that PRP might be effective as an anti-inflammatory agent, providing an attractive basis for regeneration of articular cartilage, and two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
319
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(338 citation statements)
references
References 55 publications
10
319
1
8
Order By: Relevance
“…Other basic science research demonstrated that PRP causes inhibition of the transactivating activity of nuclear factor-κB (NF-κB) and decreased expression of cyclooxygenase-2, which are important inflammatory regulators. 13 These findings suggest that PRP has the ability to stimulate local host cartilage and improve repair. Anitua et al examined the effect of a platelet-derived preparation rich in growth factors (PRGFs) in OA synovial cell biology and revealed the ability of PRGF to stimulate HA synthesis, driving the secretion of HA by the synovial fibroblasts.…”
Section: Rationale Behind the Use Of Prp For Degenerative Cartilage Dmentioning
confidence: 96%
“…Other basic science research demonstrated that PRP causes inhibition of the transactivating activity of nuclear factor-κB (NF-κB) and decreased expression of cyclooxygenase-2, which are important inflammatory regulators. 13 These findings suggest that PRP has the ability to stimulate local host cartilage and improve repair. Anitua et al examined the effect of a platelet-derived preparation rich in growth factors (PRGFs) in OA synovial cell biology and revealed the ability of PRGF to stimulate HA synthesis, driving the secretion of HA by the synovial fibroblasts.…”
Section: Rationale Behind the Use Of Prp For Degenerative Cartilage Dmentioning
confidence: 96%
“…It also stimulates the proliferation and chondrogenic [11], adipogenic and myogenic differentiation of mesenchymal stem cells, also promotes neuronal differentiation [12] and induces a chemotactic effect on vascular endothelial cells. In addition, it has also been demonstrated that hepatocyte growth factor (HGF), mainly present in the plasma, stimulates cell proliferation [13] and migration while inhibits NF-B, a key nuclear factor implicated in inflammatory responses [14]. It is also remarkable the influence of HGF as an antifibrotic mediator [15,16].…”
Section: Letter To the Editormentioning
confidence: 99%
“…In addition, Kakudo et al showed that activated platelet-rich plasma contains large amounts of PDGF-AB and TGF-β1 that promote the proliferation of human adipose-derived stem cells and human dermal fibroblast in vitro [32]. Lastly, Bendinelli et al reported the anti-inflammatory effect of PRP by a reduction of COX2 and CXCR4 gene expression [33].…”
Section: Discussionmentioning
confidence: 99%